An exploration of gender equity in household: A case from a peatland-based community in Riau, Indonesia - TUTI HERAWATI; DEDE ROHADI; MAMAT RAHMAT; BONDAN WINARNO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Herawati T, Rohadi D, Rahmat M, Winarno B. 2019. An exploration of gender equity in household: A case from a peatland-based community in Riau, Indonesia. Biodiversitas 20: 853-861. Gender roles in peatland-based communities’ livelihoods are an important factor in livelihood vulnerability due to challenging characteristics for conducting agriculture in this area. This article reports on a study of gender roles in Riau Province in 7 villages in 3 districts, aiming to identify significant attributes that determining gender equity at the household level. The data was collected through structured interviews in 221 households, in-depth interviews and Focus Group Discussions in every village. The research indicated that gender roles in agricultural activities are significantly dominated by men, while women play a more significant role in domestic activities. Both men and women contribute equally in the social life of the community; women’s participation and group membership is equal to men’s. Poor families tend to have higher gender equity in agricultural activities than rich households. The role of women in wealthier households is not in their physical contribution on the land but is mostly transformed into a decision making role. This indicates that women have a significant role in family livelihoods for both poor and rich families, but in different forms.